Frequent CTNNB1 or PIK3CA Mutations Occurred in Endometrial Endometrioid Adenocarcinoma With High Levels of Microsatellite Instability and Loss of MSH2/MSH6 Expression. Issue 4 (April 2020) - Huang, Hsien-Neng; Kuo, Chun-Wei; Lin, Ming-Chieh; Mao, Tsui-Lien; Kuo, Kuan-Ting
Abstract : Background: DNA mismatch repair (MMR) proteins form 2 heterodimers—MutSα formed by MSH2 and MSH6, and MutLα by MLH1 and PMS2. In endometrial endometrioid adenocarcinomas, cases with MMR protein defect also usually harbor other recurrent genetic mutations of the neoplasm. However, it remains unknown whether defects of the 2 functionally different heterodimers are linked to mutations in different genes. We aimed to study the MMR protein expression, microsatellite instability (MSI), and other common genetic mutations of endometrial endometrioid adenocarcinoma. Materials and Methods: We investigated the MSI status of 107 endometrial endometrioid adenocarcinoma patients. MMR protein expression, and mutation of KRAS, CTNNB1, and PIK3CA were also evaluated by immunohistochemistry and sequencing. Results: An overall 34.6% (37/107) of endometrial endometrioid adenocarcinomas were MSI-H. All MSI-H tumors exhibited loss of MMR protein expression (loss of MLH1, PMS2, MSH6, and MSH2 was noted in 22, 25, 12, and 7 cases, respectively). CTNNB1, PIK3CA, and KRAS mutation were present in 9, 7, and 7 MSI-H tumors. Compared with patients with loss of PMS2 and/or MLH1 expression, patients with loss of MSH6 and/or MSH2 expression were associated with higher frequencies of CTNNB1 mutation ( P =0.036) and PIK3CA mutation ( P =0.025). Conclusions: In MSI-H endometrial endometrioid adenocarcinomas, different types of MMR protein deficiency indicate different molecular genetic alterations.